Improvement on geometry and hemodynamics of coronary artery bypass grafting : numerical and experimental studies - Xiong, Fangli (2008)
Impaired local hemodynamics associated with unfavorable anastomotic geometry has been implicated in the initiation and progression of intimal hyperplasia and atherosclerosis, the two vascular diseases for failing bypass anastomoses. Focused on the distal coronary anastomosis, this thesis seeks to determine critical hemodynamic wall parameters that indicate disease-susceptible sites as well as to optimize anastomotic geometry and hemodynamics pertaining to long-term graft viability. Numerical simulation and in vitro experimentation using Particle Image Velocimetry were employed to study pulsatile flows in coronary anastomotic models.